The main direction of development the water legislation in Ukraine in ХХ century - Чуприна, Ю. А. (Problems of legality, 2015)
The article outlines the main directions, stages in the development of water legislation, analyzed the basic complex acts, considered the formation and development of the system of public water management authorities, traced the formation of the body acts on the responsibility for the protection and rational use of water resources.